Cultivation Of Zooplankton: Microalgae as A Valuable Feed Source - Khujamshukurov Nartoji Abduxaliqovich; Sattarov Abdumurod Sattarovich (Zien Journals, 2021)
The aim of this study is to study the protein and fat storage of Daphnia magna when used in microalgae as a food source for industrial cultivation. It is known that in world practice it is widely used in the production of protein biomass from Chlorella, Ankistrodesmus and Scenedesmus microalgae, as well as in the cultivation of zooplankton (Daphnia, Moina) under artificially controlled conditions. From zooplankton, the culture of Scenedesmus quadricauda is widely used in the reproduction of species such as Daphnia magna, pulex and longispina. Based on the studies, the morphological and biological properties and average sizes of algologically purified microflora were determined depending on the generation
Keywords: Daphnia; Chlorella; Scenedesmus; Ankistrodesmus